Coronavirus disease (COVID-19): The impact and role of mass media during the pandemic - Arriaga, P.; Esteves, F.; Pavlova, M. A.; Piçarra, N. (Frontiers in Psychology, 2021)
Mass media have long been credited as powerful sources that can shape how people experience the world and themselves. Given the unprecedented global health and social crisis created by the coronavirus disease 2019 (COVID-19), our research topic invited researchers to address the Impact and Role of Mass Media During the Pandemic. Important contributions were published in a total of 15 articles, involving 61 authors from 8 different countries, which were organized in four main lines of research: 1) the use of media in public health communication, 2) the diffusion of false information, 3) the compliance with the health recommendations, and 4) how media use relates to mental health and wellbeing. Overall, these publications showed the positive and the negative role of mass media on consumers, and the major concerns and benefits of the diversity of communicative channels in the context of the COVID-19 pandemic crisis.